Socioeconomics Factors Associated with the Utilization of Primary Health Services of Mothers and Children at Nunukan District, North Kalimantan - Kristiani, Yunita; Tamtomo, Didik; Wijaya, Mahendra (Journal of Maternal and Child Health, 2018)
Background: One of the main health development agenda in Indonesia 2015 to 2019 is reduction in maternal mortality ratio and infant mortality rate, and improve access and quality of maternal and child health services. However, variance in socioeconomics status between individual and between rural-urban have caused to difference in utilization of health service. This study aimed to analyze socioeconomics factors associated with the utilization of primary health services of mothers and children at Nunukan District, North Kalimantan. Subjects and Method: This was an analytic observational study with cross-sectional design. The study was conducted at six community health centers in Nunukan, North Kalimantan, from October to November, 2017. A total sample of 208 mothers was collected using multistage random sampling. The dependent variables were antenatal care (ANC) service, place of birth delivery, and basic immunization. The independent variables were maternal education, maternal employment status, family income, family welfare, and residence. The data were collected by questionnaire and analyzed by path analysis. Results: Utilization of ANC increased with better family welfare (b= 1.42; 95% CI= 0.34 to 2.49; p=0.010). Use of basic immunization increased with higher maternal education (b= 0.71; 95% CI= 0.06 to 1.35; p= 0.032). Place of birth delivery at formal health facility increased with living in urban area (b= 3.2; 95% CI= 1.97 to 4.44; p <0.001), maternal employment (b= 2.34; 95% CI= 0.77 to 3.91; p=0.003), and regular ANC (b=1.04; 95% CI= -0.10 to 2.18; p=0.074). Family income increased with higher maternal education level (b= 1.21; 95% CI= 0.50 to 1.92; p= 0.001) and maternal employment (b= 2.54; 95% CI= 1.67 to 3.41; p <0.001). Family welfare increased with living in urban area (b= 1.4; 95% CI= 0.09 to 2.68; p=0.035) and higher family income (b=2.5; 95% CI= 0.44 to 4.54; p= 0.017). Maternal employment status increased with higher maternal education level (b= 2.45; 95% CI= 1.63 to 3.26; p <0.001). Conclusion: Utilization of ANC directly increases with better family welfare. Utilization of basic immunization increases with higher maternal education. Place of birth delivery at formal health facility increases with living in urban area, maternal employment, and regular ANC. Keyword: social economics factors, ANC, place of birth delivery, basic immunization, mother, children